Die koninkryk van God in die Ou Testament: ’n Kort oorsig - Daniel F. O'Kennedy (In die Skriflig, 2021)
The kingdom of God in the Old Testament: A brief survey. The kingdom of God is a central concept in the teaching of Jesus, but the question posed by this article is the following: What does the Old Testament say about the kingdom of God? Several Old Testament terms convey the concept of kingdom, kingship and rule of God. This article focuses on the Hebrew and Aramaic ‘technical’ terms for kingdom: mamlākâ, malkût, mělûkâ and malkû. One finds only a few Old Testament references where these terms are directly connected to God, most of them in the post-exilic literature: 1 Chronicles 17:14; 28:5; 29:11; 2 Chronicles 13:8; Psalm 22:29; 103:19; 145:11–13; Daniel 2:44; 3:33 (4:3); 4:31 (4:34); 6:27; 7:14, 18, 27; Obadiah 21. A brief study of these specific references leads to a few preliminary conclusions: The kingdom of God refers to a realm and the reign of God, the God of the kingdom is depicted in different ways, God’s kingdom is eternal and incomparable with earthly kingdoms, the scope of the kingdom is particularistic and universalistic, the Old Testament testifies about a kingdom that is and one that is yet to come, et cetera. It seems that there is no real difference when comparing the ‘kingdom of God’ with the ‘God is King’ passages. One cannot unequivocally declare that ‘kingdom of God’ is the central concept in the Old Testament. However, we must acknowledge that Jesus’s teaching about the kingdom of God did not evolve in a vacuum. His followers probably knew about the Old Testament perspective on the kingdom of God.